Market Structure and Advertising in the Savings and Loan Industry - Lapp, John S. (The Review of Economics and Statistics, 1976)
A DVERTISING is a subject that has held considerable interest for economists, especially with respect to the relationship between and market structure. It is commonly alleged that is inconsistent with perfect competition, but is to be found where there is monopolistic competition (however, see -Telser, 1964). A correlation between and market structure will be expected under two hypotheses which differ with respect to the direction of causality: (1) can act as a barrier to entry which allows market power to be developed; and, (2) is found under monopolistic competition as a result of optimization in light of the demand curves faced by market participants. This paper considers the second hypothesis; specifically, that as market structure in SMSAs deviates further from perfect competition, savings and loan associations (SLAs) make greater use of to attract deposits. The savings and loan industry provides a good data set since entry is determined by state and federal regulatory bodies. Thus, market structure can be taken as a given variable to which SLAs react rather than as an endogenous variable that may have been influenced by advertising. We can, therefore, specifically test the hypothesis that market structure affects in the absence of a simultaneous relationship in which affects market structure. In addition, the concept of market structure is expanded to consider the effect that branching by SLAs may have on advertising. The hypothesis that market structure is a causal factor in the decision can be derived from a model of the determination of the optimal price and expenditure for a monopolist, given that the demand for the product is a function of as well as price. The ratio of expenditures to sales revenue (referred to as advertising intensity) depends on the price elasticity of demand and the marginal value product of advertising.' This result may be expressed as,